Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12879-022-07251-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD4+ T cell count is associated with lower anal human papillomavirus prevalence among HIV-positive male cohort in Taizhou, China: a cross-sectional study

Abstract: Objectives This study aims to investigate the association between CD4+ T cell count and combined antiretroviral therapy (cART) with the prevalence of anal human papillomavirus (HPV) infection among HIV-positive male cohort in China. Methods A survey was conducted in men from a HIV cohort in Taizhou, China between 2016 and 2019. A face-to-face questionnaire interview was administered, and an anal-canal swab was collected for HPV genotyping. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(42 reference statements)
2
1
0
Order By: Relevance
“…However, men taking EFV+3TC+TDF treatment (Efavirenz, Lamivudine, and Zidovudine) did not show a significant increase in CD4+ cells or clearance of HPV infection. This confirms that CD4+ cells are important in eliminating HPV infections [ 123 ].…”
Section: Natural Hpv Immune Response In Mensupporting
confidence: 76%
“…However, men taking EFV+3TC+TDF treatment (Efavirenz, Lamivudine, and Zidovudine) did not show a significant increase in CD4+ cells or clearance of HPV infection. This confirms that CD4+ cells are important in eliminating HPV infections [ 123 ].…”
Section: Natural Hpv Immune Response In Mensupporting
confidence: 76%
“…Our previous study reported that the use of cART and an increase in CD4 þ T-cell count were associated with lower prevalence of anal infection with high-risk HPV in the same population [36]. In the current study, those with CD4 þ T-cell cell count higher than 500 cells/ml at HIV diagnosis showed lower HPV prevalence, incidence, persistence rate and higher HPV clearance rate.…”
Section: Discussionsupporting
confidence: 53%
“…A meta-analysis showed that cART was negatively correlated with anal high-risk HPV prevalence in people with HIV [46]. The improvement of the immune function represented by increased CD4 + T-cell count may be helpful in prevention or clearance of HPV infection, which also showed the importance of timely cART treatment in people with HIV [36]. As all participants from this study were under cART, we examined whether different antiviral drugs were associated with HPV incidence or clearance, and no significant association was detected.…”
Section: Discussionmentioning
confidence: 99%